Antibody targeting of Cathepsin S induces antibody-dependent cellular cytotoxicity - Kwok, Hang Fai (BioMed Central, 2011)
BACKGROUND: Proteolytic enzymes have been implicated in driving tumor progression by means of their cancer cell microenvironment activity where they promote proliferation, differentiation, apoptosis, migration, and invasion. Therapeutic strategies have focused on attenuating their activity using small molecule inhibitors, but the association of proteases with the cell surface during cancer progression opens up the possibility of targeting these using antibody dependent cellular cytotoxicity (ADCC). Cathepsin S is a lysosomal cysteine protease that promotes the growth and invasion of tumour and endothelial cells during cancer progression. Our analysis of colorectal cancer patient biopsies shows that cathepsin S associates with the cell membrane indicating a potential for ADCC targeting. RESULTS: Here we report the cell surface characterization of cathepsin S and the development of a humanized antibody (Fsn0503h) with immune effector function and a stable in vivo half-life of 274 hours. Cathepsin S is expressed on the surface of tumor cells representative of colorectal and pancreatic cancer (23%-79% positive expression). Furthermore the binding of Fsn0503h to surface associated cathepsin S results in natural killer (NK) cell targeted tumor killing. In a colorectal cancer model Fsn0503h elicits a 22% cytotoxic effect. CONCLUSIONS: This data highlights the potential to target cell surface associated enzymes, such as cathepsin S, as therapeutic targets using antibodies capable of elicitingADCC in tumor cells.